Resultados da atenção farmacêutica no Brasil: Uma revisão - Ambiel, Ingrid Stephanie Stein [UNESP]; Mastroianni, Patrícia de Carvalho [UNESP] (My University, 2013)
The practice of pharmaceutical care (PC) is recent in Brazil and little is known about its impact on the health system or patients. The aim of this review was thus to identify the clinical, humanistic and economic outcomes achieved by the practice of PC in Brazil. In order to assess those outcomes, data published in studies from 1997 to 2011 were collected from Lilacs and MEDLINE databases, using the technique of content analysis. Original studies on PC that included pharmacotherapeutic follow-up were considered eligible for this descriptive review. A total of 306 articles were identified through the chosen descriptors. Of those, ten studies were eligible for this review and only two did not report significant results. The others reported increased adherence to pharmacotherapy, resolution of pharmacotherapeutic issues and control of clinical parameters of diseases (such as maintenance or reduction of blood pressure, reduction in HIV viral load and increase in lymphocyte count), promoting improvements in the general state of health and behavioral changes. However, economic impact was not assessed in any article analyzed, nor was a direct measurement of life quality performed. Although there are few studies on the outcomes of pharmaceutical care services in Brazil, it is demonstrated in this review that positive results were obtained when the pharmacist acted as a provider of optimized pharmacotherapy. This may be considered a result of the actions that followed the Brazilian Pharmaceutical Care Consensus of 2002, such as the restructuring of the curricular basis of pharmacy courses. From this point on, Brazilian researchers and pharmacists should think of a strategy to expand the offer of pharmaceutical care beyond academia and reach people in general who need this type of health care.
Outcomes of pharmaceutical care in Brazil: A literature review
Keywords: Brazil; Clinical outcomes; Pharmaceutical care